Editorial: a step forward in refining prognostication for patients with HIV‐associated hepatocellular carcinoma—Authors' reply. Issue 1 (11th December 2017) - Pinato, D. J.; Bräu, N.; Bower, M.
Abstract : Linked Content This article is linked to Pinato et al and Giannini papers. To view this article visithttps://doi.org/10.1111/apt.14356 andhttps://doi.org/10.1111/apt.14374 .